DEVELOPMENT OF EARTHQUAKE DEMONSTRATION TOOL AS A PHYSICS SCIENCE LEARNING MEDIA - Wuly Gunawan; M Nor; Hendar Sudrajad (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2020)
The creation of interactive learning activities can be influenced by the availability of media and learning resources as a useful tool in teaching and learning activities. The effectiveness of students' absorption of difficult and complicated learning materials can be achieved with the help of the demonstration tool as a media. The purpose of this research is to produce an earthquake demonstration tool, as a valid learning media for use in the learning process of physics in junior high schools. This development research uses the R & D method which was adapted from Nieveen & Folmer with three-phase, namely: preliminary research, development or prototyping phase, and the formative evaluation within the development stage. The evaluation of the validation of the media uses the instrument of validation of the earthquake demonstration tool with 5 indicators and the assessment of validation of the guidebook with 4 indicators. The results of the design of the media obtained the validation score for the earthquake demonstration tool with a score of 4.5 where a very valid category and the handbook obtained a validation score of 4.4 with a very valid category. Based on the results of this research, an earthquake demonstration tool had been successfully made and a guidebook for its use as a physics science learning media is valid and suitable for use in junior high schools.